Whole-mount immunofluorescent labeling of the adult fly retina - Hsiao, Min-Chun; Huang, Ting-Yi; Yu, Bo-Hua; Chang, Tse-Chia; Chang, Hui-Yun; Sang, Tzu-Kang (STAR protocols, 2022)
The adult Drosophila compound eye is an ideal in vivo model for studying biological questions. However, light microscopy of this tissue requires cumbersome embedding and sectioning. Here, we document detailed whole-mount procedures for immunolabeling the adult retina, enabling high-quality studies of fluorescent-tagged targets with straightforward preparations. We describe the steps for visualizing the nuclear lamina, membrane-associated protein, and actin-rich rhabdomere, but this robust protocol can apply to other cellular structures and target proteins. For complete details on the use and execution of this protocol, please refer to Chang et al. (2021). [Display omitted] •Reproducible protocol to study fluorescent-marked targets in adult Drosophila retina•Utilizes straightforward immunolabeling and mounting techniques•Can be performed in pupal eyes with modified tissue isolation procedures Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. The adult Drosophila compound eye is an ideal in vivo model for studying biological questions. However, light microscopy of this tissue requires cumbersome embedding and sectioning. Here, we document detailed whole-mount procedures for immunolabeling the adult retina, enabling high-quality studies of fluorescent-tagged targets with straightforward preparations. We describe the steps for visualizing the nuclear lamina, membrane-associated protein, and actin-rich rhabdomere, but this robust protocol can apply to other cellular structures and target proteins.